A facile one pot route for the synthesis of imide tethered peptidomimetics. Issue 2 (28th October 2015) - Panduranga, Veladi; Prabhu, Girish; Kumar, Roopesh; Basavaprabhu; Sureshbabu, Vommina V.
Abstract : A simple and efficient method for the synthesis of N, N '-orthogonally protected imide tethered peptidomimetics is presented. The imide peptidomimetics were synthesized by coupling the in situ generated selenocarboxylate of N α -protected amino acids with N α -protected amino acid azides in good yields. Abstract : A simple and efficient method for the synthesis of N, N '-orthogonally protected imide tethered peptidomimetics is presented. The imide peptidomimetics were synthesized by coupling the in situ generated selenocarboxylate of N α -protected amino acids with N α -protected amino acid azides in good yields. The protocol was also successfully applied for the synthesis of hybrid tripeptidomimetics bearing both amide and imide functionalities. In addition, coumarinic imide conjugates of amino acids have been accomplished by employing this protocol. The present method provides a convenient and easy access to imide tethered peptidomimetics and is compatible with common protecting groups employed in peptide chemistry.